PENGEMBANGAN PENGECORAN BERBAHAN BAKU PADUAN MANGANESE BRONZE UNTUK PROPELLER KAPAL YANG BERBASIS BAHAN SCRAP = CASTING DEVELOPMENT OF MANGANESE BRONZE ALLOY FOR SHIP PROPELLER BASED ON SCRAP MATERIAL - Setyadi, Iwan (BPPT, 2015)
Many attempts were made to improve the quality of ship components, in particular the ship's propeller made through little-midle industries of casting (IKM) in order to reduce dependence on imports and in order to increase local content for the national ship industries. One of the efforts is to design the material balance of manganese bronze alloy to be applied on a ship's propeller foundry by using scrap materials. In this research, the variable is the percentage level of manganese in the alloy. Achievement of optimal research results occurred in 3.27% Mn content, which obtained an increase in hardness into BHN 180.4, up 11.9% from the initial conditions with Mn content of 0.42%. While the grain size reached 130.78 ?m, or 30.6% less than the current content of 0.42% Mn. ABSTRAKBanyak upaya dilakukan untuk meningkatkan kualitas komponen kapal, khususnya baling-baling kapal yang dibuat melalui IKM pengecoran guna mengurangi ketergantungan impor dan dalam upaya peningkatan TKDN untuk industri kapal nasional. Salah satu upaya yang dilakukan adalah merancangneraca bahan paduan manganese bronze untuk diaplikasikan pada pengecoran baling-baling kapal dengan memanfaatkan bahan scrap. Dalam penelitian ini yang diatur adalah kadar prosentasi mangan dalam paduan. Pencapaian hasil penelitian yang optimal terjadi pada kandungan 3,27% Mn, dimana diperoleh peningkatan kekerasan menjadi 180,4 BHN atau naik 11,9 % dari kondisi awal dengan kandungan Mn 0,42%. Sedangkan ukuran butirnya mencapai 130,78 ?m, atau lebih kecil 30,6 % dibanding saat kandungan 0,42% Mn.